An Investigation of Noise Mitigation Strategies and Socioeconomic Status in New York City - Riddle, Johanna. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Justin Hollander, and Mary Davis.; Keywords: Public policy, and Public health.